2015
DOI: 10.1080/17542863.2014.999691
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression and related risk factors among Saudi females

Abstract: Postpartum depression (PPD) is the most common mental health complication of childbirth. It has been estimated to affect approximately 10-15% of mothers after childbirth. If untreated, PPD can lead to more serious mental illness. Identifying risk factors can help develop accurate screening assessment for the early identification and treatment of those at risk. To date, no studies have examined the prevalence rate of PPD among Saudi women or the specific risk factors for PPD in Saudi culture. The aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 9 publications
4
22
3
Order By: Relevance
“…All six additional primary studies (not mentioned in the SRs but identified by manual search) [ 72 , 73 , 74 , 75 , 76 , 120 ] clearly defined the population of interest. However, only three of them [ 74 , 75 , 76 ] defined the specific time period of the study and three [ 73 , 75 , 76 ] clarified the study setting.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All six additional primary studies (not mentioned in the SRs but identified by manual search) [ 72 , 73 , 74 , 75 , 76 , 120 ] clearly defined the population of interest. However, only three of them [ 74 , 75 , 76 ] defined the specific time period of the study and three [ 73 , 75 , 76 ] clarified the study setting.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-two primary studies [ 45 , 47 , 48 , 49 , 51 , 52 , 53 , 54 , 56 , 57 , 58 , 59 , 63 , 65 , 66 , 67 , 69 , 72 , 74 , 78 , 81 , 83 , 94 , 101 , 103 , 104 , 108 , 109 , 110 , 113 , 119 , 120 ] from 12 countries provided prevalence data during postpartum period. In addition to postpartum depression, two studies [ 10 , 124 ] included anxiety in their measurement, two studies [ 95 , 111 ] included postpartum blues, and two others combined all as “perinatal disorders” [ 67 , 98 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the cutoff point was initially established at nine in Guedeney and Fermanian’s study 12. In another study conducted in Iran by Montazeri et al, three interpretive categories were created for the scores: those with a score of ≥13 were to be considered postnatally depressed, while scores of 10–12 represented “borderline” and 0–9 “not depressed.”13 However, Al-Modayfer et al14 in Saudi Arabia reported that the optimal cutoff point was 13 among Saudi women, with a sensitivity of 40.6 and specificity of 92.7. Importantly, a recent systematic review by Shrestha et al15 noted that the potential of EPDS to identify depression among women from low- and lower-middle-income countries with different cultures is unclear.…”
Section: Methodsmentioning
confidence: 99%